A dual-mode label-free electrochemical immunosensor for ultrasensitive detection of procalcitonin based on g-C3N4-NiCo2S4-CNTs-Ag NPs. Issue 10 (6th April 2021) - Xu, Xiaoting; Li, Xuan; Miao, Juncong; Liu, Lei; Huang, Xinyi; Wei, Qin; Cao, Wei
Abstract : A novel label-free electrochemical immunosensor based on differential pulse voltammetry (DPV) and amperometric i – t curve ( i – t ) dual-mode analysis is proposed for early quantitative detection of procalcitonin (PCT). Abstract : Herein, a label-free electrochemical immunosensor based on differential pulse voltammetry (DPV) and amperometric i – t curve ( i – t ) dual-mode analysis is proposed for early quantitative detection of procalcitonin (PCT). Due to the advantages of high chemical stability and biocompatibility, graphite carbon nitride (g-C3 N4 ) was adopted as a high-capacity sensing interface to carry signal indicators. As an effective indicator of chronoamperometry, nickel cobalt sulfide (NiCo2 S4 ) was uniformly dispersed on the surface of g-C3 N4 through in-situ hydrothermal synthesis, which not only promotes the activation of bimetallic activity, but also effectively prevents the aggregation of NiCo2 S4 . At the same time, in order to establish a dual-mode analysis platform to improve accuracy and sensitivity, highly conductive carbon nanotubes (CNTs) were hybridized with composite materials to load Ag nanoparticles (Ag NPs), which have excellent oxidizing properties and are used as indicators of DPV. On account of this advanced sensing strategy, a wide linear response (DPV: 0.05 ng mL −1 –50 ng mL −1 and i – t : 1.00 pg mL −1 –10.00 ng mL −1 ) and a low detection limit (DPV: 16.70 pg mL −1 and i – t : 0.33 pg mL −1 ) are demonstrated. The immunosensor synthesized by this method has good stability and sensitivity, which could be applied in clinical diagnosis and treatment.